Chemical Functionalisation and Photoluminescence of Graphene Quantum Dots. Issue 24 (26th April 2016) - Sekiya, Ryo; Uemura, Yuichiro; Naito, Hiroyoshi; Naka, Kensuke; Haino, Takeharu
Abstract: Chemical modification of graphene quantum dots (GQDs) can influence their physical and chemical properties; hence, the investigation of the effect of organic functional groups on GQDs is of importance for developing GQD–organic hybrid materials. Three peripherally functionalised GQDs having a third‐generation dendritic wedge (GQD‐2 ), long alkyl chains (GQD‐3 ) and a polyhedral oligomeric silsesquioxane group (GQD‐4 ) were prepared by the Cu I ‐catalysed Huisgen cycloaddition reaction of GQD‐1 with organic azides. Cyclic voltammetry indicated that reduction occurred on the surfaces of GQD‐1 –4 and on the five‐membered imide rings at the periphery, and this suggested that the functional groups distort the periphery by steric interactions between neighbouring functional groups. The HOMO–LUMO bandgaps of GQD‐1 –4 were estimated to be approximately 2 eV, and their low‐lying LUMO levels (<−3.9 eV) were lower than that of phenyl‐C61 ‐butyric acid methyl ester, an n‐type organic semiconductor. The solubility of GQD‐1 –4 in organic solvents depends on the functional groups present. The functional groups likely cover the surfaces and periphery of the GQDs, and thus increase their affinity for solvent and avoid precipitation. Similar to GQD‐2, both GQD‐3 and GQD‐4 emitted white light upon excitation at 360 nm. Size‐exclusion chromatography demonstrated that white‐light emission originates from the coexistence of differently sized GQDs that have different photoluminescence emission wavelengths. Abstract : On edge : Three types of functionalised graphene quantum dots (GQDs) were synthesised by the Cu I ‐catalysed Huisgen cycloaddition reaction of an edge‐modified GQD with organic azides (see scheme). These functionalised GQDs displayed white‐light‐emission upon excitation at 360 nm. Size‐exclusion chromatography demonstrated that the white‐light emission originated from the coexistence of differently sized GQDs that emit at different photoluminescence wavelengths.